Equality and Diversity in the NHS - Mellows, Sara (2006)
The development of equal opportunities and diversity in the NHS, as a public sector organisation, have been influenced by a combination of ethical, political, legal, and economic business considerations. The principles of equality and fairness are founding principles of the NHS and are central themes of many ethical perspectives, making equality of opportunity a seemingly desirable and congruent objective. UK membership of the European Union and adoption of anti-discrimination legislation coupled with government policies and support of initiatives to redress inequalities has provided a progressive environment for the advancement of diversity. The number of individuals covered by legislation prohibiting specific types of discrimination has increased, so too have the costs to organisations of being found to be illegally discriminating, both monetarily and in terms of reputation. The business case for improving equality of opportunity, particularly emphasised by managing diversity, advocates these as cost effective strategic measures, centred around attracting, retaining and maximising the labour supply, customer satisfaction, market development and organisational success.